SISTEM PENGETAHUAN PETANI RUMPUT LAUT DI DESA GONEBALO KECAMATAN DURUKA KABUPATEN MUNA - Kasman Kasman (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
For people in the Indonesian archipelago, mainly Ghone Balano Village, the sea is the main source of income. Seaweed cultivation is one of the marine resources that have economic potential that can support the economy of the people of Ghone Balano Village, Duruka District, Muna Regency. The pest attack on seaweed cultivated by the surrounding community is a problem that needs to be resolved with the help of the local government. The data collection technique in this study is collecting data directly in the field/location to obtain objective data. The purpose of this study was to determine the utilization of marine resources by the people in the village of Ghone Balano and the role of the government in the efforts made by the community. Qualitative data was collected through in-depth interviews and observations directly in the field. The results of this study are seaweed farming business needs to get the attention of the government because the people in the coastal areas of the village of Ghone Balano still find obstacles in the location and also pests that attack cultivated seaweed.